A-Raf: A new star of the family of raf kinases. (2nd November 2015) - An, Su; Yang, Yang; Ward, Richard; Liu, Ying; Guo, Xiao-Xi; Xu, Tian-Rui
Abstract: The Ras-Raf-MEK-MAPK (mitogen-activated protein kinase)-signaling pathway plays a key role in the regulation of many cellular functions, including cell proliferation, differentiation and transformation, by transmitting signals from membrane receptors to various cytoplasmic and nuclear targets. One of the key components of this pathway is the serine/threonine protein kinase, Raf. The Raf family kinases (A-Raf, B-Raf and C-Raf) have been intensively studied since being identified in the early 1980s as retroviral oncogenes, especially with respect to the discovery of activating mutations of B-Raf in a large number of tumors which led to intensified efforts to develop drugs targeting Raf kinases. This also resulted in a rapid increase in our knowledge of the biological functions of the B-Raf and C-Raf isoforms, which may in turn be contrasted with the little that is known about A-Raf. The biological functions of A-Raf remain mysterious, although it appears to share some of the basic properties of the other two isoforms. Recently, emerging evidence has begun to reveal the functions of A-Raf, of which some are kinase-independent. These include the inhibition of apoptosis by binding to MST2, acting as safeguard against oncogenic transformation by suppressing extracellular signal-regulated kinases (ERK) activation and playing a role in resistance to Raf inhibitors. In this review, we discuss the regulation of A-Raf protein expression, and the roles of A-Raf in apoptosis and cancer, with a special focus on its role in resistance to Raf inhibitors. We also describe the scaffold functions of A-Raf and summarize the unexpected complexity of Raf signaling.